Mesothelioma of the tunica vaginalis testis: A case report - Ilke O Kazaz; Ahmet S Teoman; Sevdegul Mungan (Wolters Kluwer Medknow Publications, 2020)
Primary mesotheliomas of the tunica vaginalis testis are very rare malignant tumors. They are generally associated with exposure to asbestos. They may manifest as hydrocele, testis tumor, inguinal hernia, or epididymitis. After differential diagnosis, treatment is primarily surgical. Adjuvant therapeutic methods for mesotheliomas of the tunica vaginalis testis, with their high mortality, are controversial. Here, we present a mesothelioma case derived from tunica vaginalis testis acting as long-term pyocele with no known asbestos exposure.